EXTRAPYRAMIDAL SYNDROME: EXTRAPYRAMIDAL SYNDROME - Nadya N. Rompis; Arthur H.P. Mawuntu; Maria Th. Jasi; Rizal Tumewah (Jurnal Sinaps, 2020)
Dopamine receptor blocking agents (DRBAs), better known as antipsychotics, are drugs widely used to treat psychotic disorders. This class of drugs could cause an adverse effect consist of akathisia, dystonia, parkinsonism, and tardive dyskinesia, which is known as extrapyramidal syndrome or EPS. The first-generation antipsychotics or typical antipsychotics cause a more severe form of EPS than the second-generation antipsychotics or atypical antipsychotics. EPS is a complication that should be recognized in anti-psychotic therapy. Efforts should also be done in order to reduce the risk of EPS and performing an optimal treatment in EPS cases. This manuscript focuses in discussing the patho-mechanism, clinical features, and treatment of EPS.   Keywords: extrapyramidal syndrome, anti-psychotic, patho-mechanism, clinical features, treatment.   ABSTRAK Dopamine receptor blocking agents (DRBAs) yang lebih dikenal sebagai antipsikotik, adalah obat yang banyak digunakan untuk mengobati gangguan psikotik.  Golongan obat ini menyebabkan risiko efek samping berupa akatisia, distonia, parkinsonisme, dan diskinesia tardif, yang dikenal sebagai sindrom ekstrapiramidal atau EPS. Antipsikotik generasi pertama atau antipsikotik tipikal, menyebabkan bentuk EPS yang lebih berat dibandingkan antipsikotik generasi kedua atau antipsikotik atipikal. Sindrom ekstrapiramidal merupakan penyulit yang harus dikenali dalam terapi antipsikotik. Perlu dilakukan berbagai upaya untuk mengurangi risiko EPS serta melakukan penatalaksanaan yang optimal pada kasus EPS. Tulisan ini terutama membahas patomekanisme, gambaran klinis, dan penatalaksanaan EPS.   Kata kunci: sindrom ekstrapiramidal antipsikotik, patomekanisme, gambaran klinis, penatalaksanaan.